Mapping (in) the New Time. New Analytical-Synthetic Representations for the New n-City and its Multi-Territories (diségno, 2020)
Our cities –as translations of our societies themselves– are the most complex dynamic and informational systems that exist: they are space-time (as well as sensorial) systems constantly exchanging information among the elements that comprise them, and between the latter and the surrounding environment, mutating and fluctuating in an evolutionary manner [Gausa 2015; 2016]. (read more)